If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7x+43x-7=10(5x+10)
We simplify the equation to the form, which is simple to understand
7x+43x-7=10(5x+10)
Reorder the terms in parentheses
7x+43x-7=+(+50x+100)
Remove unnecessary parentheses
+7x+43x-7=+50x+100
We move all terms containing x to the left and all other terms to the right.
+7x+43x-50x=+100+7
We simplify left and right side of the equation.
0x=+107
0=107
The left and right sides are not equal, therefore there is no solution. This equation is invalid.
| y-6y=0 | | -1/4x+32=-x+8 | | 7(6-2a)=13+2a | | 9(8d-5)+13=12dd-2 | | u=6(7n+31)+7(n+1) | | 1/8c=-12 | | 50-2p=32+7p | | -56=c-8 | | 4x+26x-2=(5x+7) | | 2/3h-1/3h | | y-1=5/3x+10/3 | | n^2-16n-11=0 | | -56=-8 | | 4(-5m-9)=-17m+12 | | 64-7x=20x+22 | | .3333y+11=.5y-3 | | -(m^3/n^4)-5 | | 7x+9=12x-5 | | 5k-7k=12 | | 4x+12=-18+6x | | 1/2(x+10)=1/3(x+9) | | 17-6n=44+10n | | 0.2-(0.5-x)=-0.1 | | y-2=x-3 | | -4(-5m-9)=-17m+12 | | .3333+11=.5-3 | | 2x+80+x/2=1 | | 4x-12+2x+3=x | | (2/3)*(3/7) | | 7(-3+1)-(1+5-3)=0 | | (5a+10)=(3a+10) | | -7(1+3r)+3r=3-8r |